Audit Partner Tenure and Audit Quality - Carey, Peter; Simnett, Roger (The Accounting Review, 2006)
Rotation of audit partners is one of the main policy initiatives that has been implemented in many jurisdictions around the world to deal with concerns about audit quality. The basis of any requirement limiting the tenure of audit partners is that there is a reduction in audit quality associated with long periods of tenure. Using data from Australia, where the audit partner can be identified and for a period where partner rotation was not mandatory, we examine the association between audit quality and long audit partner tenure. The three measures of audit quality examined are the auditor's propensity to issue a going-concern audit opinion for distressed companies, the direction and amount of abnormal working capital accruals, and just beating (missing) earnings benchmarks. For long tenure observations we find a lower propensity to issue a going-concern opinion and some evidence of just beating (missing) earnings benchmarks, consistent with deterioration in audit quality associated with long audit partner tenure. There is no evidence of an association of long audit tenure with abnormal working capital accruals.